Evaluation of Spatial Landscape Changes for the Period from 1998 to 2021 Caused by Extreme Flood Events in the Hornád Basin in Eastern Slovakia - Gergelova, Marcela Bindzarova; Kovanič, Ludovit; Abd-Elhamid, Hany F.; Cornak, Anton; Garaj, Miroslav; Hilbert, Radovan (Land (Basel), 2023)
Tracking changes in the structure of landscape dynamics as a result of flood activity is a complex process. This study presents a model for determining changes to landscapes caused by flood events by evaluating a specific territory in Eastern Slovakia, which has been affected by repeated large-scale flood events in the past. The area has not been subject to a comprehensive monitoring of changes in the landscape structure. Based on the observation of several sets of data, a combination of statistical methods and GIS spatial analysis tools (visualizing tools for compare categories, mapping, and modelling techniques, spatial analysis models for land use change and flood modelling) were used to identify changes in the landscape structure in the period from 1998 to 2021. The results point to the significance of the year 2010, with the precipitation totals for this year showing a level significantly higher than the rolling average and confirming the occurrence of an extreme flood event. The dynamics of landscape structure changes were evaluated based on changes in the representation of selected types of land cover classes. The results of a spatial evaluation of the Corine Land Cover demonstrate that the most-significant area changes were recorded in 2012 in the pasture class, with a decrease of 31% or approximately 96.5 ha. The identified difference in the frequency of representation of individual values of the normalized differential vegetation index confirms the loss of landscape diversity and the emergence of a more homogeneous type of landscape. An assessment of the state of pastures in the study area shows that this class has completely disappeared from the site near the watercourse.